Job burnout and its relationship to achieving competitive superiority among the employees of the University of Baghdad - alShihabi, Areej Faiq Abd; Ibrahim, Noor Khalil; ALChalabi, Hassan Sabah Abdul Hassan (Heritage and Sustainable Development, 2024)
This research focuses on the epidemic of Job burnout and seeks to achieve sustainable preeminence among the employees of the University of Baghdad. It also identifies the meaning of the differences between the two genders of males and females according to the variables, and it also does the correlation between the two variables. First, the two researchers developed a test of job burnout that incorporates 18 items, which has been proven to be statistically fit. Moreover, they developed a competitive superiority measure consisting of 22 items in it, and its psychometric properties confirm their fit. The two tools were applied to a sample of 120 employees who were randomly selected from six colleges at the University of Baghdad, alongside university staff. As for API 2021–2022, the research concluded that it is found that the research sample of the employees of Baghdad University did not have any job burnout. Research reveals that females and males differ in job burnout, and it is more normal for females to be depressed, which leads to burnout in the workplace. The within-group result of the research has shown the fair competitive advantage of the University of Baghdad students. No differences in male and female brains reach significance, as institutional forces push for achieving dominant positions in competition. The results of the statistical analysis confirmed that the competitive sustainability of work belonging to the staff of the University of Baghdad does not correlate with job burnout.